Penegakan Hukum Pidana Bagi Terdakwa Pengedar Narkoba Oleh Penyandang Disabilitas Intelektual - Mei Rezky Kurnia Putra; Sulistyanta Sulistyanta (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This study aims to determine the criminal responsibility of intellectual disabilities in the legal system in Indonesia and examine how the accountability of drug dealers by people with intellectual disabilities in Decision Number 290 / Pid.Sus / 2019 / PN.Tng which decided the defendant to release and Decision Number 1364k / Pid.Sus / 2017 which decided the defendant to be imprisoned, whether the judge's consideration in deciding the two cases was in accordance with Law Number 35 of 2009 on Narcotics and Article 44 of the Criminal Code. This research is a type of normative legal research that is prescriptive and applied. This legal writing uses a statutory approach and a case approach. The technique of collecting legal materials carried out is by literature study.